Analysis for magnetic field disturbance of hybrid DC circuit breaker during breaking. (16th November 2021) - Wu, Sihang; Shen, Hong; Qi, Lei; Zhang, Bei; Cui, Xiang; Zhang, Xiangyu; Wei, Xiaoguang; Chen, Longlong
Abstract: The high current of hybrid DC circuit breaker (HCB) in the process of breaking generates strong transient magnetic field (MF), which may interfere with the normal operation of driver control units (DCUs). Therefore, the analysis for transient MF disturbance is of great significance. Due to the large space scale of HCB, with the large number of power electronic devices, the numerical calculation method has the disadvantages of large consumption of resources and slow calculation speed in solving the transient MF inside the HCB. In this study, the current generation mechanism of a 500 kV HCB is analysed, and the equivalent current path is obtained by considering the skin effect. Combined with the temporal and spatial distribution of transient current, the multi‐process transient equivalent model of transient MF calculation is established, and the model has the advantages of high precision and high speed. Then, the breaking experiment of HCB is carried out, and the transient MF near the DCU is measured. The experiment results verify the validity of the model. Furthermore, the disturbance of transient MF at the DCU of the transfer branch during breaking 25 kA current is analysed.